Challenges and opportunities for Moringa growers in southern Ethiopia and Kenya - Kumssa, Diriba B.; Joy, Edward J. M.; Young, Scott D.; Odee, David W.; Ander, E. Louise; Magare, Charles; Gitu, James; Broadley, Martin R. (Public Library of Science, 2017)
Moringa oleifera (MO) and M. stenopetala (MS) are two commonly cultivated species of the Moringaceae family. Some households in southern Ethiopia (S. ETH) and Kenya (KEN) plant MS and MO, respectively. The edible parts of these species are rich in amino acids, vitamins and minerals, especially selenium. Despite their nutritional value, Moringa is sometimes considered as a “famine food”. The aim of this study was to determine the extent of dietary utilization of these plants by Moringa Growing Households (MGHs). Moringa growing households were surveyed in 2015. Twenty-four and 56 heads of MGHs from S. ETH and KEN, respectively, were interviewed using semi-structured questionnaires. Subsistence agriculture was the main source of livelihood for all MGHs in S. ETH and 71% of those in KEN. All MGHs in S. ETH cultivated MS while those in KEN cultivated MO. Of the MGH heads in S. ETH, 71% had grown MS as long as they remember; the median cultivation period of MO in KEN was 15 years. All MGHs in S. ETH and 79% in KEN used Moringa leaves as a source of food. Forms of consumption of leaves were boiled fresh leaves, and leaf powder used in tea or mixed with other dishes. Other uses of Moringa include as medicine, fodder, shade, agroforestry, and as a source of income. Although MO and MS have multiple uses, MGHs face several challenges, including a lack of reliable information on nutritional and medicinal values, inadequate access to markets for their products, and pest and disease stresses to their plants. Research and development to address these challenges and to promote the use of these species in the fight against hidden hunger are necessary.